Conception of low-rise earthquake-resistant energy-efficient buildings; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Shefer Y. V.; Ordobaev B. S.; Romanenko S. V. Sergey Vladimirovich; Антоневич О. А. Ольга Алексеевна (2015, 2015)
Title screen